Local and systemic therapy of recurrent medulloblastomas in children and adolescents: results of the P-HIT-REZ 2005 study - Dittes, Christine; Adolph, Jonas E.; Tippelt, Stephan; Mikasch, Ruth; Obrecht, Denise; Mynarek, Martin; Rutkowski, Stefan; Pfister, Stefan; Milde, Till; Witt, Olaf; Bison, Brigitte; Warmuth-Metz, Monika; et al. (Cancers, 2022)
Recurrent medulloblastomas are associated with survival rates <10%. Adequate multimodal therapy is being discussed as having a major impact on survival. In this study, 93 patients with recurrent medulloblastoma treated in the German P-HIT-REZ 2005 Study were analyzed for survival (PFS, OS) dependent on patient, disease, and treatment characteristics. The median age at the first recurrence was 10.1 years (IQR: 6.9-16.1). Median PFS and OS, at first recurrence, were 7.9 months (CI: 5.7-10.0) and 18.5 months (CI: 13.6-23.5), respectively. Early relapses/progressions (<18 months, n = 30/93) found mainly in molecular subgroup 3 were associated with markedly worse median PFS (HR: 2.34) and OS (HR: 3.26) in regression analyses. A significant survival advantage was found for the use of volume-reducing surgery as well as radiotherapy. Intravenous chemotherapy with carboplatin and etoposide (ivCHT, n = 28/93) showed improved PFS and OS data and the best objective response rate (ORR) was 66.7% compared to oral temozolomide (oCHT, n = 47/93) which was 34.8%. Intraventricular (n = 43) as well as high-dose chemotherapy (n = 17) at first relapse was not related to a significant survival benefit. Although the results are limited due to a non-randomized study design, they may serve as a basis for future treatment decisions in order to improve the patients’ survival.
Gesehen am 22.03.2022